2005
DOI: 10.1021/ja052472p
|View full text |Cite
|
Sign up to set email alerts
|

A Family of Microporous Materials Formed by Sn(IV) Phosphonate Nanoparticles

Abstract: Reaction of Sn(IV) with phosphonic acids results in the formation of tin phosphonates with a spherical morphology arising from the aggregation of nanosized individual particles. Under high magnification, the spheres are shown to be porous with surface areas of 200-515 m2/g, depending on the type of phosphonic acid and the synthesis conditions used. The pores are largely micro in nature but also somewhat dependent on the type of phosphonic acid utilized in the preparation. Both aliphatic and aromatic organic ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 15 publications
2
53
0
Order By: Relevance
“…To overcome this problem, a new family of porous and layered Sn(IV) phenylphosphonates (SnPP) with high surface areas and 1-2 nm in pore diameters were developed [138,139], and these materials have been found to be extremely active for BV reaction of aromatic aldehydes using 30% aqueous H2O2 solution. When the SnPP catalysts were used to catalyze the BV oxidation on 4-methoxybenzaldehyde, a maximum conversion rate of 88% was observed over Sn(IV)(O3PC6H4-C6H4PO3) (SnPP-A) [140].…”
Section: Polymer Based Sn Catalystsmentioning
confidence: 99%
“…To overcome this problem, a new family of porous and layered Sn(IV) phenylphosphonates (SnPP) with high surface areas and 1-2 nm in pore diameters were developed [138,139], and these materials have been found to be extremely active for BV reaction of aromatic aldehydes using 30% aqueous H2O2 solution. When the SnPP catalysts were used to catalyze the BV oxidation on 4-methoxybenzaldehyde, a maximum conversion rate of 88% was observed over Sn(IV)(O3PC6H4-C6H4PO3) (SnPP-A) [140].…”
Section: Polymer Based Sn Catalystsmentioning
confidence: 99%
“…In addition, as opposed to silanes where Si-O-Si reactions can occur, phosphonates will not cause homo-condensations that has the advantage of increasing the grafting yield 197 . Alumina, tin oxide, zirconia and magnetite were also shown to be readily functionalized with phosphonate groups 6,214,[216][217][218] . In addition, due to larger steric hindrance effects, phosphonate groups may also form multiple anchorages onto metal oxide surfaces, further stabilizing the structure 219 .…”
Section: Phosphonatementioning
confidence: 99%
“…Corma and his group have been designing Sn-b zeolite and Sn-MCM-41 heterogeneous catalysts for the reaction of aromatic aldehydes with hydrogen peroxide, in non-halogenated solvents such as dimethylformamide and dioxane [16][17][18][19], and they have suggested that these catalysts activates the carbonyl compounds instead of the hydrogen peroxide, making them more selective. A family of porous Sn(IV) phenylphosphonates with layered structures, high surface area and pore diameters in the 10-20 Å range, have also been synthesized [20,21] and were found to be extremely active in the oxidation of different aromatic aldehydes, using 30% aqueous hydrogen peroxide, particularly in the absence of any organic solvents [22].…”
Section: Introductionmentioning
confidence: 99%